C9ORF72 hexanucleotide repeat exerts toxicity in a stable, inducible motor neuronal cell model, which is rescued by partial depletion of Pten. (1st February 2017) - Stopford, Matthew J.; Higginbottom, Adrian; Hautbergue, Guillaume M.; Cooper-Knock, Johnathan; Mulcahy, Padraig J.; De Vos, Kurt J.; Renton, Alan E.; Pliner, Hannah; Calvo, Andrea; Chio, Adriano; Traynor, Bryan J.; Azzouz, Mimoun; et al.
Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating and incurable neurodegenerative disease, characterised by progressive failure of the neuromuscular system. A (G4C2)n repeat expansion in C9ORF72 is the most common genetic cause of ALS and frontotemporal dementia (FTD). To date, the balance of evidence indicates that the (G4C2)n repeat causes toxicity and neurodegeneration via a gain-of-toxic function mechanism; either through direct RNA toxicity or through the production of toxic aggregating dipeptide repeat proteins. Here, we have generated a stable and isogenic motor neuronal NSC34 cell model with inducible expression of a (G4C2)102 repeat, to investigate the gain-of-toxic function mechanisms. The expression of the (G4C2)102 repeat produces RNA foci and also undergoes RAN translation. In addition, the expression of the (G4C2)102 repeat shows cellular toxicity. Through comparison of transcriptomic data from the cellular model with laser-captured spinal motor neurons from C9ORF72-ALS cases, we also demonstrate that the PI3K/Akt cell survival signalling pathway is dysregulated in both systems. Furthermore, partial knockdown of Pten rescues the toxicity observed in the NSC34 (G4C2)102 cellular gain-of-toxic function model of C9ORF72-ALS. Our data indicate that PTEN may provide a potential therapeutic target to ameliorate toxic effects of the (G4C2)n repeat.